Youth and sustainable development in Iraq: Challenges and options - Yassin Obaid, Mayssam (Al-Adab Journal, 2019)
Achieving sustainable development requires real efforts to keep pace with the progressive process in the world through meaningful and broad work to achieve a bright future image of Iraq in all areas of life. Achieving the sustainable development goals requires a broad youth presence to meet the challenges that have plagued Iraq, but it has not prevented the dreams of Iraqis looking forward to sustainable development, which aims to increase opportunities for people while ensuring that the freedoms of future generations are not compromised. Most emerging societies seek to reduce the vulnerability of young people and expand the circle of intervention to empower to enhance opportunities for sustainability and equity and help them to get decent jobs, build trust and enhance social capital to ensure the sustainability of development roles. The research illustrates the challenges and options for youth participation in sustainable development, a random sample of the 150 young people in Baghdad, Zafaraniyah region, was used to learn about the importance of their role in achieving sustainable development. Use a variety of methods, including interviewing and questionnaires, and a set of questions has been asked and analyzed statistically.